An Evaluation of the Efficacy of a Novel Non-Peroxide, Phthalimidoperoxycaproic Acid Teeth Whitening Agent in Conjunction with 810-nm Diode Laser - Shruti S. Kumbhare; Sachin B. Mangalekar; Priyanka Vhanmane; Shashank Vijapure; Saumya Shankar; Prasanna Sawant (Journal of Pharmacy and Bioallied Sciences)
Aim: To evaluate the efficacy of a non-peroxide (PAP) teeth whitening agent activated by an 810-nm diode laser. Materials and Methods: Fifteen patients with mild to moderate stains (Lobene index) and tooth color shades A2–A3.5 were selected. After oral prophylaxis and polishing with Opalustre paste, the PAP whitening agent was applied to the labial surfaces of maxillary anterior teeth and activated using a diode laser. Assessments were conducted at baseline, immediately posttreatment, one month, and three months for gingival index, plaque index, Lobene stain index, tooth color (Vita shade guide and Cocolux), and hypersensitivity (VAS). Results: Tooth color showed significant improvement immediately and one month posttreatment; however, by three months, the color reverted to baseline levels. Conclusion: Laser-assisted PAP bleaching demonstrated significant initial whitening with minimal adverse effects, though long-term color stability requires further evaluation.